Pergeseran Bahasa Bantik pada Kalangan Anak-Anak di Desa Bantik Sumoit Kecamatan Bolaang Timur Kabupaten Bolaang Mongondow - Syafilawati Mongilong; Moh.Karmin Baruadi; Nuramila Nuramila (Lembaga Pengembangan Kinerja Dosen, 2025)
Language contact that occurs in a multilingual society causes various linguistic events. One of these linguistic events is the language shift that occurs among children in Bantik Sumoit Village. This study aims to describe how the Bantik language shift occurs, the factors causing the Bantik language shift, and efforts to overcome the Bantik language shift among children in Bantik Sumoit Village, Bolaang Timur District. This study uses a qualitative descriptive research type located in Bantik Sumoit Village, Bolaang Timur District. The data collection technique used is by listening to direct conversations from children while recording and noting important things during the interaction process. Then data analysis is carried out by transcribing, reading, selecting data, identifying data, grouping/classifying, and making conclusions. The results of the study show that the use of the Bantik language has experienced a significant shift which is marked by indicators such as the replacement of traditional languages ​​by other languages ​​and the emergence of an imbalance in its use. This indicator indicates that language shift occurs when the use of the first and second languages ​​becomes unbalanced. If this balance is lost, there are two possibilities that can occur. First, the first language persists despite the influence of the second language. Second, the first language is replaced by the second language until it is no longer used. This is influenced by a number of factors, namely education, socio-economic conditions, environment, and family. Efforts to overcome language shift include: adding Bantik language as a local content subject (mulok) in schools, the active role of parents in using regional languages ​​in the family environment, and increasing public awareness of the importance of preserving regional languages ​​in everyday life.